The Role of Digital Transformation in Managerial Accounting Practices: Empirical Study of Indonesian Companies - Mutmainah, Mutmainah; Nadiar, Rahmi; Alfikri, Rahmatullah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This research investigates the impact of digital transformation on managerial accounting practices in Indonesian companies, aiming to enhance efficiency and decision-making accuracy by understanding how digital tools reshape accounting roles and strategic functions. Method: The study employed a mixed-method design, combining quantitative data from questionnaires distributed to 40 purposively sampled management accountants with qualitative insights from a systematic literature review. This integration of empirical data from Indonesian practitioners and synthesized knowledge from existing literature offers a holistic view, enhancing the validity and depth of understanding. Data were analyzed using descriptive statistics, regression, and thematic synthesis. Results: Findings show that digital transformation significantly improves financial reporting accuracy and speeds decision-making. Human resource readiness and strategic technology integration are identified as key success factors. Implications: The research highlights how digital adoption enhances financial control and competitiveness. It provides practical guidance for firms on continuous training and robust cybersecurity policies, potentially informing industry best practices and regulatory frameworks for digital accounting in Indonesia. Novelty: This study uniquely integrates empirical quantitative data directly from Indonesian managerial accountants with a comprehensive systematic literature review, offering fresh, context-specific insights into digital accounting transformation not extensively covered by prior global studies.